FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PENCAPAIAN K4 DI DESA SUMBEREJO WONOAYU SIDOARJO: FACTORS THAT INFLUENCE THE ACHIEVEMENT OF K4 IN SUBEREJO VILLAGE WONOAYU SIDOARJO - Cholifah, Cholifah; Putri, Navyati Asrita (Jurnal Kebidanan Midwiferia, 2015)
Indonesia’s K4 coverage in 2014 was 86.85%, while the national target of K4 should reach 95%. This indicates that K4 coverage is still low. So it needsfurther research that aimed to analyze the factors influenced the achievement of K4 in the Sumberejo village Wonoayu Sidoarjo.This study was designed using retrospective analytic survey with cross sectional approach. The populationswere all mothers who had given birth in Sumberejo village in January-December 2014 period as amount 42 people. The sampling was used probability sampling, with simple random sampling technique, consist of 38 people. The data were analyzed using a computer program with logistic regression statistics The results of the study were not at risk of maternal age (76.3%), half of secondary education (44.7%), Unemployed (68.4%), parity was not at risk (94.7%), good and enough knowledge level (47,7%), did not get full support from the family (60.5%), capable to reach health services (94.7%), K4 has been reached (68.4%). Variables were not related to the achievement of K4 as age, occupation, parity, family support, and affordability of health care to the mother, while education and knowledge was the related variable. Variables that influence together towards the achievement of K4 were knowledge and education of (57.5%).The conclusion of educationand knowledge research was influenced together towards the achievement of K4. The health workers were expecting to give information about pregnancy visit in order to reach K4.